Dentin bond strength evaluation between a conventional and universal adhesive using etch-and-rinse strategy - Genine Moreira de Freitas Guimarães; Karin Cristina da Silva Modena; Carolina Yoshi Campos Sugio; Tamires de Luccas Bueno; Maria Angélica Silvério Agulhari; Maria Teresa Atta (Universidade Estadual de Campinas, 2021)
Aim: The aim of this study was to compare the microtensile bond strength (μTBS) and the characteristics of the adhesive interface of Scotchbond Universal - SU - etch-and-rise mode (3M ESPE) and Adper Scotchbond Multi-Purpose - MP (3M ESPE) to dentin over time. Methods: Class I cavity preparations were performed in 60 human molars that were randomly divided according to the dentin bonding system (DBS) used (n=30): (1) Acid conditioning + SU and (2) Acid conditioning + MP. For bonding strength (BS) analysis, 30 teeth (n = 15) were sectioned into sticks and submitted to the microtensile test in a universal testing machine after 24 hours and 12 months. The adhesive interface of the others 30 teeth was analyzed in a confocal microscope after 24 hours and 12 months. The data of μTBS were analyzed by two-way repeated measures ANOVA and Tukey's HSD (α = 0.05). Results: SU presented the lowest DBS compared to MP (p=0.000). Time did not influenced DBS for both adhesive systems (p=0.177). Confocal microscopy analysis showed no cracks between both adhesive systems tested. Conclusion: The results indicate that MP - μTBS showed a better performance compared to SU in total-etch mode.